The impact of electronic prescribing systems on clinical pharmacy practice - Alzahrani, Turki Ibrahim; Binsaad, Jaman Saad; Almasabi, Abdullah Ahmed; Alharthi, Faeyz Musleh; Alqarni, Abdullah Salem; Albaqami, Salman Nasser; Alqahtani, Muhannad Saeed; Aljabry, Iman (International Journal Of Community Medicine And Public Health, 2024)
This review explores the impact of electronic prescribing (e-prescribing) systems on clinical pharmacy practice, highlighting the potential benefits and challenges associated with their use. Medication errors, a significant concern within healthcare settings, have been shown to decrease with the adoption of e-prescribing, offering a promising tool to enhance patient safety and reduce adverse drug events. However, the transition from traditional handwritten prescriptions to electronic methods introduces new challenges, including the emergence of new types of errors, such as incorrect drug selection, and potential increases in mortality rates, as observed in pediatric patient. Furthermore, it discusses the limited exploration of e-prescribing in primary care and community pharmacy settings, areas that require further investigation to fully understand the benefits and burdens of e-prescribing use. By examining barriers related to person, tasks, environment, tools and technologies, and organizational factors, this review emphasizes the importance of considering various aspects that influence the efficacy and safety of e-prescribing systems. The findings suggest a critical need for incorporating human factors principles in the design and evaluation of these systems to ensure they effectively support clinical pharmacy practice and enhance patient care.